2014
DOI: 10.1097/bot.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Wound Complications Associated With Bone Morphogenetic Protein-2 in Orthopaedic Trauma Surgery

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…RhBMP‐2 is traditionally loaded on to a collagen sponge and it has been hypothesized that the rapid release of the Bone Morphogenetic Protein (BMP) from the sponge limits its osteoinductive activity . In order to overcome this limitation, high doses of rhBMP‐2 are used clinically which has been associated with reports of postoperative complications including heterotopic bone formation, soft tissue swelling and osteolysis …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RhBMP‐2 is traditionally loaded on to a collagen sponge and it has been hypothesized that the rapid release of the Bone Morphogenetic Protein (BMP) from the sponge limits its osteoinductive activity . In order to overcome this limitation, high doses of rhBMP‐2 are used clinically which has been associated with reports of postoperative complications including heterotopic bone formation, soft tissue swelling and osteolysis …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] In order to overcome this limitation, high doses of rhBMP-2 are used clinically which has been associated with reports of postoperative complications including heterotopic bone formation, soft tissue swelling and osteolysis. 10,11 3D printed scaffolds represent a promising approach for bone repair. 3D printed scaffolds can be customized to fit complex anatomic skeletal defects.…”
Section: Introductionmentioning
confidence: 99%
“…However, the supraphysiologic doses of rhBMP used in clinical practice and the kinetics of BMP release from the carrier [2] are associated with inconsistent clinical results and several complications [3,4,5]. Previous animal studies using a mouse critical-sized femoral defect model in our laboratory have demonstrated that treatment with rhBMP-2 leads to healing of the defect, with the bony bridge gradually becoming thinner at later time points (28 and 56 days after treatment) [6].…”
Section: Introductionmentioning
confidence: 99%
“…78 Likewise, Chan et al found significantly higher wound complication rates among the rhBMP-2 treatment group (31%) than among the control group (18%). 79 Further analysis of complications in posterior fusion surgeries illustrates a fivefold increase (2.1% vs. 0.4%) in wound complications associated with BMP-2 use during a posterior approach. 80 Infections, both local and systemic, are known complications of all invasive procedures.…”
Section: Wound Complications With Bmp-2mentioning
confidence: 99%